Intra-Operative Bone Stability Test. Issue 4 (December 2018) - Iobst, Christopher A.; Bunhor, Darvin; Skaggs, David L.; Frick, Steven L.
Abstract : Fractures of the supercondylar humerus are the most common elbow fracture in pediatrics. Management of this injury would be aided if surgeons could reliably test fracture stability intraoperatively after pinning. A transverse supracondylar humerus fracture model was created using 3 adult cadaver upper-extremity specimens with an intact soft tissue envelope. Using the lateral entry technique, three 2.0 mm pins were then drilled using lateral entry technique to create an "A" pinning. Pins were checked in anteroposterior and lateral views with the C-arm to confirm accurate placement in both planes. The pinning configuration was then tested by holding the proximal fragment steady with one hand and applying stress to the distal fragment with the other hand. The amount of movement of the distal fragment relative to the proximal fragment was recorded for each specimen. Distraction did not produce any substantial displacement of the osteotomy. The most valuable maneuvers were (in order of effectiveness): external rotation, lateral translation, posterior translation, valgus, and apex posterior. The results of this study indicate that external rotation, lateral translation, posterior translation, and valgus stresses created the most temporary deformity to the construct. A combination of these maneuvers should help the surgeon to decide if the fixation is stable. Our study demonstrates a possible technique to determining intraoperatively the stability of fixation of supracondylar humerus fractures, which could prevent the need for postoperative radiographs to assess stability.